An alternative membrane topology permits lipid droplet localization of peroxisomal fatty acyl-CoA reductase 1 - Exner, Tarik; Romero-Brey, Inés; Stremmel, Wolfgang; Bartenschlager, Ralf; Poppelreuther, Margarete; Füllekrug, Joachim (Journal of cell science, 2019)
Skip to Next Section - Fatty acyl-CoA reductase 1 (Far1) is a ubiquitously expressed peroxisomal membrane protein that generates the fatty alcohols required for the biosynthesis of ether lipids. Lipid droplet localization of exogenously expressed and endogenous human Far1 was observed by fluorescence microscopy under conditions of increased triglyceride synthesis in tissue culture cells. This unexpected finding was supported further by correlative light electron microscopy and subcellular fractionation. Selective permeabilization, protease sensitivity and N-glycosylation tagging suggested that Far1 is able to assume two different membrane topologies, differing in the orientation of the short hydrophilic C-terminus towards the lumen or the cytosol, respectively. Two closely spaced hydrophobic domains are contained within the C-terminal region. When analyzed separately, the second domain was sufficient for the localization of a fluorescent reporter to lipid droplets. Targeting of Far1 to lipid droplets was not impaired in either Pex19 or ASNA1 (also known as TRC40) CRISPR/Cas9 knockout cells. In conclusion, our data suggest that Far1 is a novel member of the rather exclusive group of dual topology membrane proteins. At the same time, Far1 shows lipid metabolism-dependent differential subcellular localizations to peroxisomes and lipid droplets.